Mary R. Musgrove letter to Thomas H. Kent regarding spring bird sightings, April 29, 1983 - Musgrove, Mary R.et al (1983)
Letter from Mary R. Musgrove to Thomas H. Kent regarding spring bird sightings, April 29, 1983. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1983. Epson - sheet feed